2019
DOI: 10.3329/bjms.v18i3.41638
|View full text |Cite
|
Sign up to set email alerts
|

Status of Vitamin D by measuring 25 - Hydroxyvitamin D level in Dhaka City

Abstract: Background and aims: Vitamin D deficiency is associated with skeletal as well as extraskeletal diseases. Aim of this study was to find out the status of Vitamin D level in a densely populated area like Dhaka. Method: This descriptive cross sectional study was conducted in Ibn Sina Medical College Hospital in Kallyanpur, Dhanmondi Ibn Sina Hospital and Ibn Dina Diagnostic Laboratory in Dhanmondi. Total 500 subjects who went for vitamin D assay were included in this study. Serum Vitamin D (25 - Hydroxyvita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…This provides a reason for argues between the scientists that vitamin D deficiency is a potential risk factor for CVD, MS, obesity, and diabetes. 11,12 According to literature, vitamin D deficiency plays an important role in the pathogenesis of MS risk factors, which, in turn, directly affects the cardiovascular system. It also contributes to the emergence and progression of insulin resistance and disorders in the function of adipose tissue, which results in obesity, stimulates the rennin angiotensin-aldosterone system, and promotes hypertension.…”
Section: Research Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This provides a reason for argues between the scientists that vitamin D deficiency is a potential risk factor for CVD, MS, obesity, and diabetes. 11,12 According to literature, vitamin D deficiency plays an important role in the pathogenesis of MS risk factors, which, in turn, directly affects the cardiovascular system. It also contributes to the emergence and progression of insulin resistance and disorders in the function of adipose tissue, which results in obesity, stimulates the rennin angiotensin-aldosterone system, and promotes hypertension.…”
Section: Research Materials and Methodsmentioning
confidence: 99%
“…It also contributes to the emergence and progression of insulin resistance and disorders in the function of adipose tissue, which results in obesity, stimulates the rennin angiotensin-aldosterone system, and promotes hypertension. 12,16 However, the data available today on this issue are rather contradictory, which does not allow stating unequivocally the positive effect of vitamin D on the reduction of cardiovascular risk and the risk of MS, as well as on the course of the CVD. insulin resistance reduction in metabolic syndrome and does not reduce the risk of adverse (fatal and non-fatal) cardiovascular events.…”
Section: Research Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies suggest that vitamin D deficiency is a pandemic condition in healthy people even in areas of abundant sunshine 5 . A recent study conducted in the city of Dhaka found a prevalence of 43.8% of vitamin D deficiency among unselected people 6 . Two studies published from Bangladesh also found around one third of patients with DM with vitamin D deficiency 7,8 .…”
Section: Introductionmentioning
confidence: 99%